Neuropathic Pain in Children with Sickle Cell Disease: The Hidden Side of the Vaso-Occlusive Crisis - Jeanne Sigalla; Nathalie Duparc Alegria; Enora Le Roux; Artemis Toumazi; Anne-Françoise Thiollier; Laurent Holvoet; Malika Benkerrou; Sophie Dugue; Berengere Koehl (Children, 2021)
The majority of hospitalizations of patients with sickle cell disease (SCD) are related to painful vaso-occlusive crises (VOCs). Although the pain of VOC is classically nociceptive, neuropathic pain (NP) has also been demonstrated in SCD patients. The aim of our study is to specify the prevalence of NP during VOCs in SCD children using a dedicated scale and to measure its characteristics. We performed a prospective study that included SCD children hospitalized for an acute VOC. The presence of NP was sought with the DN4 scale on the second and fourth days of hospitalization. A total of 54 SCD children were included in the study. Overall, 41% of the patients (n = 22) experienced neuropathic pain during the VOC, mostly at an early stage (Day 2). The median age, the sex ratio, the location of the pain, and the morphine consumption were similar for patients with and without NP. Our study shows that neuropathic pain is very common during VOCs in SCD children. The absence of identified risk factors should prompt us to be vigilant regardless of the patient’s age, sex, and clinical presentation.